Etnoekologi dalam Buku Kumpulan Dongeng Desa Telayap Pelalawan Riau Karya Noni Andriyani - Aprilla, Yaiza Ike Aprilla (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
Human relations with the environment for a long time then gave birth to various characteristics of society by the characteristics of the environment which is seen as culture. The culture is strongly influenced by the availability of natural resources in the environment. This study aims to analyze, interpret, describe and conclude ethnoecology in the Book Collection of Fairy Tales in Pelalawan Riau Village by Noni Andriyani. This research is ethnographic research with a descriptive method. This research method is used to describe and analyze the forms of words, phrases, clauses, sentences, and paragraphs that contain ethnoecology. The data was taken from the book Collection of Fairy Tales in Pelalawan Riau Village by Noni Andriyani using hermeneutic data collection techniques. Based on the analysis and discussion of the research, it can be concluded that the elements of culture related to ethnoecology are in the form of a religious system, a livelihood system, and a living/technology equipment system in the Book of the Collection of Fairy Tales in Pelalawan Riau Village by Noni Andriyani. The elements of culture related to ethnoecology that is more dominant in this fairy tale are ethnoecology in living equipment systems/technology because living equipment/technology such as objects used in everyday life are more helpful for them in fulfilling their life needs and helping them in terms of livelihood.